Endovascular stenting of traumatic extracranial carotid artery dissections in the pediatric population - Chern, Joshua J. (2009)
Background Traumatic extracranial carotid artery injuries are rare in children. Treatment options include surgery, anticoagulation therapy and endovascular treatment. There have been only limited reports in the literature documenting endovascular carotid stent placement in the pediatric population. In these reports, stent deployment was utilized in the setting of pseudoaneurysm formation. Case report Here we report a case of endovascular carotid stenting for traumatic carotid dissection in a 15 year-old boy. An uncovered bare self-expanding stent was used to treat progressive high-grade stenosis in the early post-injury period. Conclusion At 6 months post-procedure, complete healing of the carotid artery was demonstrated on follow-up angiogram.